2011
DOI: 10.1111/j.1742-1241.2010.02590.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of patient barriers to insulin

Abstract: The insulin barriers perceived by patients with diabetes evolved with their disease experience. While administration was the primary preference driver for insulin-naïve patients, patients were increasingly concerned with more clinically relevant barriers as they gained experience with insulin. This finding suggests that patients using insulin understand the importance of achieving an optimal balance between safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…Similarly to our results, they demonstrated a preference for pills over parenteral (IV) routes of administration in RA patients. Our findings are thus generally in line with their study,43 and add to similar findings with other diseases using different methodologies 1113. However, the ability of Augustovski et al43 to quantify exactly the relative importance of oral administration was limited, due to the coding procedure they used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly to our results, they demonstrated a preference for pills over parenteral (IV) routes of administration in RA patients. Our findings are thus generally in line with their study,43 and add to similar findings with other diseases using different methodologies 1113. However, the ability of Augustovski et al43 to quantify exactly the relative importance of oral administration was limited, due to the coding procedure they used.…”
Section: Discussionsupporting
confidence: 91%
“…In other chronic diseases, there is evidence to suggest that parenteral modes of administration are associated with certain barriers perceived by patients, which in turn may lead to reduced adherence to prescribed treatments 1113. Therefore, real-life efficacy of treatments will depend not only on their clinical efficacy but also on treatment characteristics impacting on patient adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous preference studies of patients' preferences for attributes of T2DM medications have included a wide range of attributes and levels, but generally consistent results have been reported including the finding that glucose control [ , ] and weight change were attributes of high importance to patients with T2DM. The high level of importance reported for efficacy in the current study is also consistent with previous research, suggesting that patients' self‐reported treatment satisfaction is significantly related to improvements in HbA1c control .…”
Section: Discussionmentioning
confidence: 83%
“…If most participants were not yet using any oral medications for their condition, then the idea of insulin initiation may be not particularly concerning to them. Participants with diabetes on insulin may have fewer attitudes to insulin intensification compared with those starting it, although many may still have similar concerns about its side effects [39,40]. Thus, attitudes that affect patients' adherence to insulin therapy or its intensification, as well as differences in attitudes of insulin therapy between insulin-naive and insulin-treated patients, should be studied.…”
Section: Discussionmentioning
confidence: 95%